Pelaksanaan Eksekusi Hak Tanggungan Akibat Wanprestasi Dalam Perjanjian Kredit di Bank BRI (Studi Putusan Nomor 1/Pdt.GS/2023/PN BAN) - Laily Maghfiroh; Nawalia Azahra; Syifadilla Subagyo Putri; Muhammad Dewanto Adi Saputra; Muhammad Rahmadzani Hidayat; Dwi Aryanti Ramadhani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The aim of this research is to analyze and understand the elements of default in credit agreements at Bank BRI and the execution of mortgage rights due to default in credit agreements at Bank BRI. The research uses a normative juridical approach and a qualitative research method based on previous journals and prevailing regulations in Indonesia. Default occurred because the debtor did not pay installments on time and showed no intention to settle the debt. The execution of mortgage rights is divided into six types, including claiming, direct private sale, private auction by the creditor, auction through an auction office without court involvement, court fiat execution, and ordinary civil lawsuit through the court. Decision number 1/Pdt.GS/2023/PN Ban executed the auction through a civil lawsuit.